1276. Evaluation of CD377, a Novel Antiviral Fc-Conjugate (AVC), In Vitro Activity and In Vivo Efficacy in Immune-Competent and -Deficient (SCID) Lethal Mouse Models. (31st December 2020) - Levin, James; Amundson, Karin; Borchardt, Allen; Lam, Thanh; Brady, Tom; Abelovski, Elizabeth; Döhrmann, Simon; Cole, Jason; Ong, Voon; Tari, Les
Abstract: Background: Cidara's AVCs are novel, potent, antiviral agents conjugated with the Fc domain of human IgG1. CD377 is an AVC development candidate being evaluated for prevention and treatment of seasonal and pandemic influenza, including in immune-deficient populations unable to benefit from vaccination. We evaluated CD377 in vitro and in SCID mice to determine the impact of compromised immune status on efficacy. Methods: CD377 and comparators (oseltamivir [OS], zanamivir [ZA], baloxavir marboxil [BM]) were evaluated in vitro by neuraminidase inhibition (NAI), and cytopathic effect (CPE) assays. The pharmacokinetics (PK) and efficacy of CD377 were determined in immune-competent (IC; BALB/c) and immune-deficient (ID; BALB/c SCID) mice. Efficacy was assessed by intranasal challenge at 3x the LD95 of influenza A/Puerto Rico/8/1934 (H1N1), followed by a single subcutaneous (SC) dose of CD377, 2 hours post-challenge. The SCID study also evaluated the efficacy of BM at 3 mg/kg (BID x 1 day). Body weights (BW) were monitored for 21 days, with 20% BW loss recorded as mortality. Results: In vitro evaluation by NAI showed CD377, OS, and ZA to be approximately equipotent, with IC50 values between 0.5 and 1.7 nM. However, by CPE, CD377 was 4.5-fold more active than BM and >1, 000-fold more active than OS and ZA. In vivo, the PK of CD377 was found to be comparable in IC and ID mice. In subsequent efficacy studies, CD377 was protective at 0.1 mg/kg in IC mice (P=0.0020 vs. vehicle), while control groups fully succumbed to infection by Day 7 (Fig. 1A). In a similar study with ID mice, CD377 dosed at 0.1 mg/kg was also fully protective (P=0.0020). In contrast, mice treated with 6 mg/kg (total dose) of BM were only partially protected until day 13 (40% mortality by study end) (Fig. 1B). The potency of CD377 was further supported by BW data, which mirrored the survival data in both studies. Conclusion: CD377 exhibited potent in vitro activity and had similar PK in IC and ID mice. In efficacy studies, CD377 demonstrated robust potency in both IC and ID mouse models at equivalent doses (0.1 mg/kg, SC, single dose). These results support further development of CD377 as a novel antiviral for the prevention and treatment of influenza infection, including in people with immune deficiencies and higher risk of infection. Balb/c and Balb/c SCID Disclosures: James Levin, PhD, Cidara Therapeutics (Shareholder) Karin Amundson, B.S., Cidara Therapeutics (Shareholder) Allen Borchardt, PhD, Cidara Therapeutics (Employee) Thanh Lam, PhD, Cidara Therapeutics (Shareholder) Tom Brady, PhD, Cidara Therapeutics (Shareholder) Elizabeth Abelovski, B.S., Cidara Therapeutics (Shareholder) Simon Döhrmann, PhD, Cidara Therapeutics (Shareholder) Jason Cole, PhD, Cidara Therapeutics (Shareholder) Voon Ong, PhD, Cidara Therapeutics, Inc. (Employee, Shareholder) Les Tari, PhD, Cidara Therapeutics (Shareholder)